FIGURATIVE LANGUAGE USED IN SELENA GOMEZ’S SONG LYRICS: A SEMANTIC ANALYSIS - Clarisca Carolina Simarmata; Herman Herman; Dumaris E. Silalahi (STKIP PGRI Jombang, 2021)
It was the goal of this study to figure out what kinds of figurative language Selena Gomez's song lyrics contain and to found out the interpretation in those songs. There wer six songs of Selena Gomez chosen to be the source of data, namely: Lose you to love me, Vulnerable, Wolves, Let me get me, People you know, Back to you. To collect the data, browsing the website Genius.com, searched the scripts of the song lyrics and copying and printing the song lyrics as data. Qualitative research was used in this study. Document or content analysis is a common application for this technique. Analyzing the data included various steps such as classifying it, describing it, tabulating it, and drawing conclusions from it. As a technique for verifying the validity of the data, the researchers in this study used data triangulation. Overall, Selena Gomez's song lyrics had 44 figurative language analysis data points. There were 3 (7%) data of simile, 20 (45%) data of metaphor, 2 (5%) data of personification, 2 (5%) data of metonymy, 3 (7%) data of symbol, 2 (5%) data of paradox, 11 (25%) data of hyperbole and 1(1%) data of irony. Through this research, the researcher would like to suggest people to analyze figurative language in the song, because figurative language is an interesting subject to study and analyze. In each types of figurative language are having other meaning. That is why the researcher thinks it is important for English student who want to know more about meaning especially about figurative language.